Investigating the drivers of failure of research-industry collaborations in open innovation contexts. (January 2023) - Puliga, Gloria; Urbinati, Andrea; Franchin, Enrico Maria; Castegnaro, Stefano
Abstract: Collaboration between research and industry is fundamental for technology innovation. Most existing research in this domain has focused on the drivers or enabling factors that lead to the success of such collaboration. On the contrary, the lack of information about collaboration failures in research-industry settings still represents one of the main obstacles to studying this topic. In this paper, we argue that management scholars should deepen inquiry on unsuccessful research-industry collaborations, as these occurrences may also have major repercussions in terms of business failures. Accordingly, we take stock of research on unsuccessful collaborations in the Big Science context, a special open innovation environment characterised by unexplored cases of research-industry collaboration failures. To address the need to investigate the drivers of failure in this context, we leverage a multiple case study analysis with a retrospective approach of a polar sample type of six case studies of collaborations between CERN – the biggest fundamental research organisation in the world – and supplier companies: three collaborations that have been recognised as successful, and three that have been recognised as failures. By doing so, we aim to provide a framework highlighting the main drivers that lead to failures of collaborations in this peculiar open innovation context and to shed light on the reasons why research-industry collaborations may fail in the Big Science context. Highlights: Investigation of the failure of research-industry collaborations in the peculiar Open Innovation context of Big Science. Drivers of failures are focalisation and exclusion, short term orientation, competence stand-by, and passive and indirect participation . Multiple case study analysis with a polar sample type of successful and unsuccessful collaborations between CERN and supplier companies. Practical implications for how to effectively manage Big Science projects in Open Innovation collaborations.